The Later Wittgenstein on Language and its Role in the Constitution of Reality. Its Connection with the Previous Philosophical Tradition. - Tomashpolskaia, Natalia (UMA Editorial, 2024)
This dissertation examines the later Wittgenstein¿s ideas on language and its role in the constitution of reality and the influence of the previous philosophical tradition on the development of these ideas. I have analysed in detail the role of language in the constitution of reality in later Wittgenstein, his central concepts of the later period and cover the resemblances of the later Wittgenstein¿s ideas on language and reality and the views of his contemporaries on this subject matter. I argue that the problem of the constitution of reality in the later Wittgenstein is relevant and it is still under- researched among scholars, as opposed to the analogous matter with the early Wittgenstein of Tractatus Logico- Philosophicus. I have described `Wittgensteinian Linguistic Turn¿ and the transition from the logical construction of reality in early Wittgenstein to the anthropological constitution of reality in his later thought. In my research, I show the strong relationship between the later Wittgenstein¿s ideas and the Continental philosophical tradition. I shall argue that Wittgenstein¿s philosophical thought was developing in the entire stream of the Continental philosophical tradition. Moreover, if early Wittgenstein¿s ideas significantly influenced the development of analytic philosophy and logical analysis of language, his later ideas and concepts found an immediate response in the continental though in the different areas of humanities: philosophy of language, anthropology, sociology, hermeneutics, epistemology, phenomenology, arts, etc.
Keywords: Wittgenstein, Ludwig - Crítica e interpretación - Tesis doctorales; Filosofía; Filosofía del lenguaje; Historia de la filosofía